CONJUGATION OF IMPERFECTIVE VERBS OF THE SECOND CONJUGATION IN THE PRESENT TENSE (Web of Teachers: Inderscience Research, 2026)
In the paper, development of a practical class on the base of the methodology being created for the 1st year students of the major Theory and Practice of Translation (English) is described. The class has been held in eight students’ groups at Alisher Navoyi Tashkent State University of the Uzbek Language and Literature. The objective of the class is training and mastering in exercises the verbs which are conjugated by analogy, which helps the students understand and memorize them, as well as actively use them in oral and written communication. Also, etymological links of the Russian and English words are analyzed in the paper to use them as mnemonic devices to easily memorize the new lexical units on the base of associations.